Chemical Investigations of Differentially Oxidized Polycylic Pyrroles from Bipolaris Fungi: Synthetic Entry Into the Bipolamine Alkaloids. (8th August 2022) - Xuan, Jun; Machicao, Paulo A.; Haelsig, Karl T.; Maimone, Thomas J.
Abstract: indolizidine alkaloids of unusual biosynthetic origin have recently been characterized from several species of fungi within the Pleosporaceae family. Possessing distinct polycyclic architectures with two embedded electron‐rich pyrroles as well as reported antibacterial activity against gram positive and negative pathogens, these natural products represent attractive targets for total synthesis. Herein we survey the differential functionalization of a chemically sensitive bispyrrole framework resulting in the preparation of multiple bipolamine alkaloids, work which sheds light on their innate chemical reactivity and potential biosynthetic relationships. Abstract : Antibacterial alkaloids from Bipolaris Fungi represent notable challenges to the field of chemical synthesis owing to their reactive, electron‐rich bispyrrole architectures. Herein we explore the chemical reactivity of this unusual alkaloid framework resulting in the total synthesis of bipolamines D, E, G, and I and a discussion surrounding possible biosynthetic relationships within this family.